Challenges of Female Students in Time Management in Learning at State Islamic University - Daflaini, Daflaini; Fidya, Yatti (al-fikrah: Jurnal Manajemen Pendidikan, 2024)
The article aims to find out and analyse the challenges of female students’ dual role of time management in learning at the State Islamic University. This article uses qualitative research methods. Research on female students’ time management model in dealing with academic procrastination was conducted with a type of field research. Data were collected by interviewing female students with dual roles at the State Islamic University. In addition, data from literature review was also used to find various references related to the research implementation process, especially those correlated with procrastination, time management, and women’s dual roles. The data analysis techniques used are data condensation, data presentation, and conclusion drawing. This article found that academic procrastination experienced by female students has an impact on students’ academic obligations. Efforts to overcome the existence of procrastination can be carried out through forming ideal time management during the dual role that women struggle in undergoing lectures.